1995
DOI: 10.1111/j.1365-2672.1995.tb01670.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sewage sludge treatment processes on oocysts of Cryptosporidium parvum

Abstract: The effect of common sewage sludge treatment processes on oocysts of the coccidian protozoan Cryptosporidium was evaluated in laboratory simulations. The ability of primary sewage sedimentation to remove Cryptosporidium oocysts was found to be poor. Thermophilic (55 degrees C) aerobic digestion and sludge pasteurization at the same temperature were found to be effective treatments to inactivate Cryptosporidium oocysts. Approximately 10% of the oocyst population were found to be viable after 18 d exposure to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 9 publications
0
24
0
2
Order By: Relevance
“…However, the previously described effects of heat on the infectivity of ova and oocysts (26,37) on May 11, 2018 by guest http://aem.asm.org/ log 10 unit should guarantee reductions in the numbers of infectious oocysts of parasites to levels below the levels required by some guidelines (34,35). The results presented here suggest that after calibration studies it should be possible to determine the ranges for inactivation of naturally occurring bacteriophages that guarantee a range of reduction in the number of Salmonella cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the previously described effects of heat on the infectivity of ova and oocysts (26,37) on May 11, 2018 by guest http://aem.asm.org/ log 10 unit should guarantee reductions in the numbers of infectious oocysts of parasites to levels below the levels required by some guidelines (34,35). The results presented here suggest that after calibration studies it should be possible to determine the ranges for inactivation of naturally occurring bacteriophages that guarantee a range of reduction in the number of Salmonella cells.…”
Section: Discussionmentioning
confidence: 99%
“…This data contrasts with that of Stadterm an et al (1995) who found that anaerobic digestion at 37ÊC inactivated 90% of the oocysts within 4 h and 99.9% of the oocysts within 24 h. The contrastin g data may not only represent difference s in the anaerobic digester and isolate or age of oocysts used, but may also represent difference s in the techniques for assessing viability. Whereas Whitmore and Robertson (1995) utilised a vital dye technique for assessing viability with verificatio n by in vitro excystatio n, Stadterma n et al (1995) relied upon an in vitro exeystation technique with enumeration of sporozoites.…”
Section: Sludgementioning
confidence: 99%
“…Research on inactivatio n of Cryptosporidium oocysts during treatment of sludge has indicated that both therm ophilic aerobic digestion and sludge pasteuris ation at 55ÊC were effective treatments (Whitmore and Robertson, 1995) with complete inactivatio n at first sampling (24 h and 2 h respectiv ely). However, in a mesophilic anaerobic digester, although within the first three days die off was relatively rapid with approximately 80% reduction in viability, after 18 days a small proportion of the oocysts remained viable.…”
Section: Sludgementioning
confidence: 99%
“…• C) aerobic digestion was effective at inactivating the oocysts of Cryptosporidium (108). Mesophilic anaerobic digestion (35 • C) inactivated 90% of oocysts after 18 days.…”
Section: Transport and Viability Through Water Treatment Processesmentioning
confidence: 99%